Implementasi Pembelajaran Titilaras dalam Meningkatkan Apresiasi Musik Tradisional di Kalangan Mahasiswa - Setiaji, Denden; Suharjo, Farhan; Robby, Dzikri Alfa (JPKS (Jurnal Pendidikan dan Kajian Seni), 2025)
This research is motivated by the low interest of students in the Sendratasik Study Program at Muhammadiyah University of Tasikmalaya in traditional music. The purpose of this study is to find out how *Titilaras* learning can enhance students' appreciation for traditional music while also shaping their character as future arts educators. The method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The results show that *Titilaras* learning can improve students' understanding of traditional music and foster attitudes of discipline, responsibility, and pride in local culture. However, the learning process still faces challenges such as limited facilities and low student motivation, which indicates the need for method innovation and improvement of learning infrastructure.